2015
DOI: 10.2319/112113-857.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the length of orthodontic mini-screw implants on their long-term stability: A prospective study

Abstract: The length of the TISAD/TAD may be one of the factors that can affect the long-term success rate in the mandibles of 20- to 29-year-old women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 26 publications
1
23
0
5
Order By: Relevance
“…Since their introduction in orthodontic practice, mini-screw implants (MSIs) have been extensively used and investigated 1,2,3,4,5,6 . Previous studies have reported success rates varying from 74% to 93% 3,7,8,9,10 . However, variables that directly interfere with implant stability have remained unclear 3,5,10,11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since their introduction in orthodontic practice, mini-screw implants (MSIs) have been extensively used and investigated 1,2,3,4,5,6 . Previous studies have reported success rates varying from 74% to 93% 3,7,8,9,10 . However, variables that directly interfere with implant stability have remained unclear 3,5,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported success rates varying from 74% to 93% 3,7,8,9,10 . However, variables that directly interfere with implant stability have remained unclear 3,5,10,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Wilmes et al 7 supported this result, as the authors similarly found 1.1 mm screw stability fairly lower than 1.6 mm ones. In turn, Chen et al 8 and Sarul et al 9 , while investigating the impact of micro-implant length, concordantly reported that screws 8 mm long are more stable than 6 mm ones. Last but not least, two independent meta-analyses by Crismani et al 10 and Dalessandri et al 11 have validated these outcomes and stated that sizes of minimum 1.2 × 8 mm and 1.3 × 8 mm, respectively, ensure sufficient primary stability of micro-screws.…”
mentioning
confidence: 77%
“…There was no initial difference in grip nor in shape or strength 45,49 , be it conical or cylindrical. There is a recommended length of >8 mm at the maxilla and 6 mm at the mandible 42 ; regardless of the NEW PARAMETERS FOR IMPROVED STABILITY OVER TIME New perspectives on miniscrews: improving stability 48 . The bone-related criteria play an important role in the short-term success rate 30,31,51 .…”
Section: Doi: 101051/odfen/2016020mentioning
confidence: 99%